Analisis Literatur terhadap Peranan Konsep Diri dalam Pembentukan Kecerdasan Emosional pada Remaja - Daniel Romi Sihombing; Siti Aminah (Journal on Education, 2024)
This study provides a detailed literature analysis on the role of self-concept in shaping emotional intelligence in adolescents. The findings reveal that adolescents with a positive self-concept exhibit better abilities in recognizing and managing their emotions. A robust self-concept serves as a stable psychological foundation, enabling them to respond to emotional situations with wisdom. Additionally, social support from family and peers has proven to strengthen the relationship between positive self-concept and emotional intelligence. The research underscores the significance of cultivating a positive self-concept as a cornerstone for enhancing the emotional skills of adolescents. The implications emphasize the need for a holistic approach involving educational institutions, families, and communities to create an environment supportive of healthy emotional development in adolescents, contributing to a deeper understanding of these dynamics.